RANCANG BANGUN APLIKASI REVIEW PENGUNJUNG TERHADAP PELAYANAN HOTEL PADA THE HILLS HOTEL BATAM - Gulo, Johanes Try Oktavianus; Simalango, Holong Marisi (Journal of Digital Ecosystem for Natural Sustainability, 2021)
The services provided by the hotel support the mission of The Hills Hotel at Batam City. The critique and suggestion form provided by the hotel has a function to accommodate complaints from visitors against the waiters that the hotel has provided. The use of this criticism and suggestion form has often been ignored by visitors because it is still conventional. The purpose of developing this application is to replace the function of criticism and suggestion forms that still use paper into digital form in the form of ratings in the hope of increasing the interest of hotel visitors in providing visitor responses to hotel services. The development of this application uses the method of observation, literature study and needs analysis and the design of this application system uses the prototyping methodology. This application development uses Android Studio software and uses MySQL as a database. The design of this application uses Unified Modelling Language to describe the actions that occur in this application. Application of Visitor Response to Hotel Services as a substitute for criticism and suggestion forms serves to collect data on hotel visitor responses and the collected data will be used as material for hotel reviews in improving the quality of their servants.